15ab+25ab+-12ab=

Simple and best practice solution for 15ab+25ab+-12ab= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15ab+25ab+-12ab= equation:


Simplifying
15ab + 25ab + -12ab = 0

Combine like terms: 15ab + 25ab = 40ab
40ab + -12ab = 0

Combine like terms: 40ab + -12ab = 28ab
28ab = 0

Solving
28ab = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '28'.
ab = 0

Simplifying
ab = 0

The solution to this equation could not be determined.

See similar equations:

| 6a-2ab-8-4ab+3a= | | 11-1/3b=-6 | | 3r^2-13r-10=0 | | 21x-12+3=x-31x | | 8(x+9)-21=0 | | Y=20-16x^2+32x | | 3x^2+15x-8=0 | | x^(1/3)=3 | | 3.6=r(24) | | (4-u)(2u-5)=0 | | 8x^2+4x-3-9x^2= | | 3(5-2x)=3(5x+2) | | 7x-9=5x-53 | | 16x^2-3x-4x^2+5+10= | | 9-4(5x-7)= | | x^2+118x-378=0 | | -6x^2+2+11x^2-13-5x= | | 13-52+f=34 | | 6x-1=3y+2 | | 5(c+9)=5(c-4) | | 2(1/3)x3(2/7) | | r^2-3r=2r+14 | | 2lne+3ln(x-1)=5 | | 5y-3+y+41=6y+40-2 | | 9x^2-14x-4+3x= | | x^-2=9/16 | | 24a/4 | | 19x-3=14+2x | | x^*2=9/16 | | 24a/4= | | Y=-6+3x+x^2 | | (3y+1)=23+23 |

Equations solver categories